Downregulation of BIRC5 inhibits the migration and invasion of esophageal cancer cells by interacting with the PI3K/Akt signaling pathway - Shang, Xiaobin (Oncol Lett, 2018)
As a mitotic spindle checkpoint gene, baculoviral IAP repeat containing 5 (BIRC5) serves pivotal roles in the development of various types of malignant tumors. In the present study, the expression of BIRC5 in patients with different stages of esophageal squamous cell cancer (ESCC) was investigated. The effect of BIRC5 on the migratory and invasive abilities of different ESCC cell lines was analyzed. Additionally, the effect of BIRC5 on the angiogenesis-associated factor vascular endothelial growth factor, brain-specific angiogenesis inhibitor 1 and methyl-CpG binding domain protein 2 was examined. In addition, the interaction between BIRC5 and the phosphatidylinositol 3-kinase (PI3K)/Akt pathway was analyzed. It was determined that BIRC5 is able to inhibit the migration and invasion of tumor cells, and regulate the expression of angiogenesis-associated factors. In addition, the PI3K/Akt signaling pathway is able to regulate the expression of BIRC5, which affects the development of ESCC.